Regulation and reform of the housing finance system - Hendershott, Patric H.; Villani, Kevin E. (Washington : American Enterprise Institute for Public Policy Research, 1977)
The book analyzes government efforts to protect the housing finance system from two problems resulting from rising inflation and interest rates in 1966 - 1975
sju 22/01/2019
Loans
Keywords: Housing